Understanding the Decline in Adolescent Fertility in the United States, 2007–2012 - Lindberg, Laura; Santelli, John; Desai, Sheila (Journal of adolescent health, 2016)
The decline in U.S. adolescent fertility has accelerated since 2007. Modeling fertility change using behavioral data can inform adolescent pregnancy prevention efforts. We used data on sexual activity and contraceptive use from National Surveys of Family Growth for young women 15–19 years of age, and contraceptive failure rates, to estimate a Pregnancy Risk Index (PRI) for the periods 2007, 2009, and 2012. Logistic regression was used to test for change over time in sexual activity, contraceptive use, and PRI. Statistical decomposition was used to calculate attribution of change in the PRI to changes in sexual activity or contraceptive method use. Sexual activity in the last 3 months did not change significantly from 2007 to 2012. Pregnancy risk declined among sexually active adolescent women (p = .046), with significant increases in the use of any method (78%–86%, p = .046) and multiple methods (26%–37%, p = .046). Use of highly effective methods increased significantly from 2007 to 2009 (38%–51%, p = .010). Overall, the PRI declined at an annual rate of 5.6% (p = .071) from 2007 to 2012 and correlated with birth and pregnancy rate declines. Decomposition estimated that this decline was entirely attributable to improvements in contraceptive use. Improvements in contraceptive use appear to be the primary proximal determinants of declines in adolescent pregnancy and birth rates in the United States from 2007 to 2012. Efforts to further improve access to and use of contraception among adolescents are necessary to ensure they have the means to prevent pregnancy.